TEKNOLOGI AUGMENTED REALITY SEBAGAI INOVASI MEDIA PEMBELAJARAN AGAMA HINDU - Ni Putu Eka Merliana; Putu Bagus Adidyana Anugrah Putra; I Gede Dharman Gunawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This paper aims to provide an overview and describe the development of learning Hinduism using Augmented Reality Technology. Hindu religious education provides the basis for guiding the younger generation of Hindus to continue to do and do good as stated in the teachings of Tri Kaya Parisudha, Catur Dormitory, Tri Hita Karana and there are still Hindu religious concepts based on the Vedic scriptures. The method used in this study is a literature review analysis obtained from several libraries in the form of books, articles from journals and proceedings related to the learning process using Augmented Reality technology. The results obtained reveal that innovation in using Augmented Reality technology needs to pay attention to several things, namely the design of technology utilization, technology acceptance, understanding in utilizing Augmented Reality technology, the use and purpose of using Augmented Reality technology. The introduction of various objects in Hindu religious learning such as introducing objects and functions of the ritual facilities used by utilizing Augmented Reality technology is very helpful in delivering information to students because it can visualize objects that are not real.